Influence of different surgical concepts for moderate skeletal class II and III treatment on the nasopharyngeal airway space. Issue 10 (October 2019) - Moscarino, Samantha; Kötter, Florian; Brandt, Max; Modabber, Ali; Kniha, Kristian; Hölzle, Frank; Wolf, Michael; Möhlhenrich, Stephan Christian
Abstract: Purpose: This study aimed to compare the effects of different orthognathic and camouflage treatments for correcting moderate skeletal class II and III malocclusions on the pharyngeal airway space (PAS). Materials and methods: Lateral cephalograms of 89 patients with moderate skeletal class II and III malocclusion (WITS up to 7 mm,  −7 mm respectively) were evaluated before and after treatment. PAS was divided into 6 levels (P1: nasopharynx, P2-4: oropharynx, P5-6: laryngopharynx), and 7 groups were formed depending on the type of treatment: 1) class II, mandibular advancement; 2) class II, maxillary setback/mandibular advancement; 3) class II, upper premolar extraction; 4) class III, mandibular setback; 5) class III, maxillary advancement; 6) class III, maxillary advancement/mandibular setback; and 7) class III, lower premolar extraction. Results: Significant changes occurred only in patients with class II malocclusion (groups 1 and 2) before and after surgery in the nasopharyngeal and oropharyngeal space. Furthermore, significant differences between the patients with class II malocclusion were found when compared to the premolar extraction group: group 1 vs. group 3 (P3: −1.31 mm (SD 1.74 mm) vs. 0.89 mm (SD 1.79 mm); P4: −0.72 mm (SD 2.82 mm) vs. 1.42 mm (SD 2.16 mm); P  ≤ 0.05), group 2 vs. group 3 (P2: 0.35 mm (SD 1.96 mm) vs. 2.28 mm (SD 1.88 mm), P3: −1.31 mm (SD 1.74 mm) vs. 0.35 mm (SD 1.96 mm), P4: −0.72 mm (SD 2.82 mm) vs. 2.84 mm (SD 2.16 mm), P  ≤ 0.05). Conclusions: Orthognathic surgery in patients with moderate skeletal class II and III malocclusion seems to affect PAS only slightly. Premolar extractions for compensation (camouflage treatment) can result in a reduction of the oropharynx airway space in both types of skeletal malocclusions. Therefore, in borderline patients with presence of OSAS, orthognathic surgery should be considered.